(untitled) (Heteroglossia – studia kulturoznawczo-filologiczne, 2023)
In her novel, Juli Zeh paints the picture of a perfect world from which disease and suffering have been almost entirely eliminated and in which health becomes the overarching value. That would truly be a perfect world, wholly subordinated t the state and the dictates of health, were it not for the disobedient individuals breaking out of the system. One of such rebels and enemies of the state is the main character, Mia Holl. She becomes a symbol of freedom and independence, a personification of the right to illness, dirt and germs. In a sterile world an individual’s freedom and right of self-determination present a danger to the state’s apparatus – a totalitarian system in which nothing matters but the dictate of health.